1999
DOI: 10.1523/jneurosci.19-22-09986.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Isolation, and Promoter-Defined Separation of Mitotic Oligodendrocyte Progenitor Cells from the Adult Human Subcortical White Matter

Abstract: Previous studies have suggested the persistence of oligodendrocyte progenitor cells in the adult mammalian subcortical white matter. To identify oligodendrocyte progenitors in the adult human subcortical white matter, we transfected dissociates of capsular white matter with plasmid DNA bearing the gene for green fluorescence protein (hGFP), placed under the control of the human early promoter (P2) for the oligodendrocytic protein cyclic nucleotide phosphodiesterase (P/hCNP2). Within 4 d after transfection with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
209
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 237 publications
(217 citation statements)
references
References 54 publications
8
209
0
Order By: Relevance
“…Our study confirms the existence of such cells in the temporal lobe in numbers that closely coincide with those described by Roy and colleagues. 18 Our phenotypic analysis of the adult A2B5 ϩ cells indicate that such cells are further along the OLG lineage than their fetal counterparts but remain less differentiated in vitro than the mature OLGs isolated from the adult human CNS. This comparative analysis was performed after cells were maintained in culture for 5 to 7 days under relatively basal culture conditions supplemented with growth factors (bFGF and T3) that are considered to promote cell survival and proliferation rather than differentiation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our study confirms the existence of such cells in the temporal lobe in numbers that closely coincide with those described by Roy and colleagues. 18 Our phenotypic analysis of the adult A2B5 ϩ cells indicate that such cells are further along the OLG lineage than their fetal counterparts but remain less differentiated in vitro than the mature OLGs isolated from the adult human CNS. This comparative analysis was performed after cells were maintained in culture for 5 to 7 days under relatively basal culture conditions supplemented with growth factors (bFGF and T3) that are considered to promote cell survival and proliferation rather than differentiation.…”
Section: Discussionmentioning
confidence: 78%
“…Roy and colleagues, 18 reported that progenitor cells (ganglioside A2B5-positive) comprised 3 to 5% of the total cell population derived from human adult temporal lobe resections and could undergo a limited number of cell divisions in vitro. OLGs could be derived only from the A2B5 ϩ population, although this population could also give rise to neurons and astrocytes.…”
mentioning
confidence: 99%
“…Multi-potential precursors are abundant in many regions of the adult brain parenchyma [31][32][33][34]. In particular, oligodendrocyte progenitor cells (OPCs) were isolated from various regions of the adult rodent CNS [35][36][37], and were identified also in the adult human brain [38][39][40][41][42] and spinal cord [43]. OPCs are identified by expression of chondroitin-sulfate proteoglycan NG2+ and of platelet-derived growth factor receptor-α are highly abundant in the adult CNS, comprising up to 5% of its cells [37].…”
Section: Glial Progenitor Cells In the Adult Central Nervous Systemmentioning
confidence: 99%
“…An alternative approach that may circumvent the potential negative effects of prolonged in vitro cell expansion may be by high scale selective isolation of precursor cells. For example, precursor cells could be isolated from dissociated fetal and adult CNS tissue by transfection with a plasmid encoding green fluorescent protein (GFP) placed under the control of the 2′,3′-cyclic nucleotide 3′-phosphodiesterase-2 (CNP2) promoter, a regulatory element activated in early oligodendrocyte progenitor cells, followed by fluorescence activated cell sorting [40,42,127]. Alternatively, fluorescence-activated or immunomagnetic sorting were used to isolate A2B5(+)/poly-sialic acid-neural cell adhesion molecule (PSA-NCAM)(−) fetal and adult human glial progenitors [42].…”
Section: Cell Replacementmentioning
confidence: 99%
“…It is of interest that OPCs are proliferative cells and that most of them differentiate into postmitotic oligodendrocytes that do not proliferate (Temple and Raff 1986;Roy et al 1999). Therefore, Hsp90 is present at the cell surface at the proliferative stage in both OPCs and neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%